1969
DOI: 10.1007/bf00633288
|View full text |Cite
|
Sign up to set email alerts
|

Oils of the seeds of Sambucus nigra

Abstract: Sambucus nigra (European elder) of the family Caprffoliaceae is distributed in the European part of the dSSR, in the Caucasus, in Western Europe, and the Mediterranean region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1976
1976
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Moreover, the positional distribution of fatty acids in triacylglycerols could affect the nutritional value of lipids [14]. The available scientific reports on Sambucus berries refer to the composition of phenolic compounds [6,11,15] and their anti-oxidant properties [10,12], but few studies relate to lipid compositions [12,16,17,18,19]. The study of Sambucus fruit seed oils for their main lipid constituents (neutral and polar), may lead to value-added utilization of these fats and enhance the profitability of the fruit processing industries.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the positional distribution of fatty acids in triacylglycerols could affect the nutritional value of lipids [14]. The available scientific reports on Sambucus berries refer to the composition of phenolic compounds [6,11,15] and their anti-oxidant properties [10,12], but few studies relate to lipid compositions [12,16,17,18,19]. The study of Sambucus fruit seed oils for their main lipid constituents (neutral and polar), may lead to value-added utilization of these fats and enhance the profitability of the fruit processing industries.…”
Section: Introductionmentioning
confidence: 99%
“…The results varied according to the species or the genotypes. Otherwise, Gigienova et al (1969) reported that Sambucus nigra (Elderberry) seeds contain 38.49% linoleic acid (ω-6) and 36.25% linolenic acid (ω-3). The findings of these researchers were different from those of this study.…”
Section: Resultsmentioning
confidence: 99%
“…The characterization of seed oils of S. canadensis, S. nigra, and S. racemosa has been reported by Schuette and Brooks (1936), Gigienova et al (1969), andJohansson et al (1997), respectively. The amount of extractable oils is significant (ca.…”
Section: Foodmentioning
confidence: 99%